Manajemen Peserta Didik Sekolah Dasar (Studi Multi Situs pada SDN Paringin Selatan 1 dan SD IT Darul Fikri Kabupaten Balangan) - Wartinah Wartinah; Aslamiah Aslamiah; Sulaiman Sulaiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to describe student management including student admission planning, student development and student evaluation at SDN Paringin Selatan 1 and SD IT Darul Fikri, Balangan Regency. This research is qualitative research in the form of case studies at 2 sites, namely SDN Paringin Selatan 1 and SD IT Darul Fikri. The research data sources are school principals and teachers. Data collection was carried out through interviews, observation and documentation and then analyzed using within-site data analysis, individual site analysis and cross-case data analysis. Checking the validity of the data was carried out by source triangulation. The research results from 2 research sites illustrate that student admission planning includes stages starting from analyzing student needs, such as planning the number of students who will be accepted, forming a new student admissions committee and holding promotions and outreach, implementing the School Environment Introduction Period (MPLS). Developing students by creating a comfortable and conducive learning atmosphere, integrating the general curriculum with character and religious education values. Organizing extracurricular activities as a means of channeling students' talents and potential. Student evaluations, attitude competency evaluations, knowledge competency and skill competency evaluations are all contained in evaluation reports in the form of student report cards, remedial implementation and teacher performance evaluations. The conclusion of this research is that student recruitment planning includes: analysis of student needs, student recruitment planning, student selection, student orientation and reporting of new student data. Student development includes coaching in the learning process, coaching in extracurricular activities and coaching students in discipline. Student evaluation includes the development of children's knowledge, reports on children's learning outcomes, remedial activities and evaluation of teacher performance. Keywords: Elementary School Students, Management olah Dasar